Ordinance no. 1, § 8, THE MINING ECHO, Jul. 7, 1877 at 1 (Empire City, Kansas). - (:unkn) unknown (General Publisher, 1870)
Any person who shall, while exercising the right to carry firearms, not concealed, be intoxicated, or shall do any act or thing calculated to cause apprehension or alarm to any citizen within the limits of this city shall be deemed guilty of a misdemeanor, and upon conviction be fined in a sum not less than $3.00 nor more than $20.00.
--
Keywords: POSSESSION - DANGEROUS PERSONS